Pengaruh Kadar Air terhadap Beberapa Sifat Fisik Biji Lada Putih - Andi Muhammad Akram Mukhlis; Edy Hartulistiyoso; Yohanes Aris Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The physical properties of seed are required in designing an apparatus for handling, separation, drying, storage, and processing. The physical properties of white pepper seeds were determined as a function of moisture content in the range of 15,40 - 64,80 % dry basis (d.b.). The average height, length and width at a moisture content condition of 15,40 % (d.b.) were 4,11 ± 0,27 mm; 4,35 ± 0,34 mm and 4,35 ± 0,35 mm, respectively. In the range of moisture content 15,40 - 64,80 % (d.b.), the results of this study showed an increase linearly of the third axial dimension, the average diameter, the roundness from 0,969 to 0,977, the volume from 39,50 to 67,34 mm3, the surface area from 55,87 to 79,92mm2 and the thousand seed mass from 52,47 to 75,63 g. Bulk density and true density has a polynomial correlation with changes in moisture content.The porosity decreased from 45,01 % to 44,88 % with an increase in the moisture content range of 15,40 - 64,80 % (d.b.). ABSTRAKSifat fisik biji-bijian diperlukan dalam merancang suatu peralatan untuk penanganan, pemisahan, pengeringan, penyimpanan dan pengolahannya. Sifat fisik biji lada putih ditentukan sebagai fungsi kadar air pada rentang 15,40 - 64,80 % basis kering (b.k.). Tinggi, panjang dan lebar rata-rata pada kondisi kadar air 15,40 % (b.k.) adalah 4,11 ± 0,27 mm; 4,35 ± 0,34 mm dan 4,35 ± 0,35 mm berturut-turut. Pada rentang kadar air 15,40 - 64,80 % b.k., hasil penelitian ini menunjukkan peningkatan secara linear pada ketiga dimensi aksial, diameter rata-rata, kebulatan dari 0,969 hingga 0,977, volume dari 39,50 hingga 67,34 mm3, luas permukaan dari 55,87 hingga 79,92 mm2 dan massa seribu biji dari 52,47 hingga 75,63 g. Bulk density dan true density memiliki hubungan polinomial dengan perubahan kadar air biji. Porositas menurun dari 45,01 % hingga 44,88 % dengan peningkatan kadar air pada rentang 15,40 - 64,80 % (b.k.).